2018
DOI: 10.1002/pbc.27505
|View full text |Cite
|
Sign up to set email alerts
|

Weak correlation of bleeding scores to platelet electron microscopy: A retrospective chart review of pediatric patients with delta‐storage pool disorder

Abstract: Background Delta granule storage pool deficiency (δ‐SPD) is a rare platelet disorder in which a deficiency of platelet granules leads to poor aggregation, resulting in varying clinical bleeding phenotypes. Children with δ‐SPD have variable laboratory results, making the proper diagnosis and evaluation controversial. Objectives To describe the demographic and laboratory trends of this population and to assess the value of electron microscopy in diagnostic evaluation and its correlation to bleeding symptoms. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(245 reference statements)
0
8
0
Order By: Relevance
“…The BAT has been refined by ISTH working groups and is a valuable screening tool to determine the relative severity of abnormal bleeding, but it is unable to discriminate specific etiologies of unexplained bleeding [ 2 ]. The BAT has a poor correlation to δ-SPD [ 28 ]. Well-defined algorithms have been established to diagnose platelet dysfunction disorders [ 3 , 6 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BAT has been refined by ISTH working groups and is a valuable screening tool to determine the relative severity of abnormal bleeding, but it is unable to discriminate specific etiologies of unexplained bleeding [ 2 ]. The BAT has a poor correlation to δ-SPD [ 28 ]. Well-defined algorithms have been established to diagnose platelet dysfunction disorders [ 3 , 6 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We concentrated on determining the number of platelets required to avoid an erroneous result, as a correlation between DB averages and the severity of bleeding symptoms is reportedly absent. 11 We found that utilization of a case-specific algorithm (Figure 4) would eliminate the chance of an incorrect diagnosis while markedly decreasing the number of full 100-platelet counts. The effectiveness of this method is 84%.…”
Section: Discussionmentioning
confidence: 76%
“…The most frequently ordered tests for platelet function evaluation are light transmission aggregometry and PFA-100 with lumiaggregometry and flow cytometry being less widely used. 9 It has been reported that PFA-100 does not correlate with the presence or severity of δ-SPD and should not be used alone for screening. 16 At our center, we obtain PFA-100 along with PEM as part of the secondary bleeding workup.…”
Section: Discussionmentioning
confidence: 99%